Hypoalbuminaemia at time of surgery is associated with an increased risk for overall graft loss after kidney transplantation. Issue 8 (25th April 2019) - Anderson, Benjamin; Khalil, Khalid; Evison, Felicity; Nath, Jay; Sharif, Adnan
ABSTRACT: Aim: The aim of this retrospective cohort study was to investigate whether pre‐operative hypoalbuminaemia (<35 g/L) is associated with adverse outcomes post‐kidney transplantation. Methods: Our retrospective, single‐centre analysis included all patients who received their kidney transplant between 2007 and 2017, with documented admission albumin levels prior to surgery. Survival analyses were undertaken to explore the relationship of pre‐transplant hypoalbuminaemia versus other baseline variables upon post‐transplant outcomes. Results: We analysed 1131 kidney allograft recipients transplanted at our centre (2007–2017), with median follow‐up 746 days (interquartile range 133–1750 days). Kidney transplant recipients with pre‐operative hypoalbuminaemia were more likely older, female, recipients of deceased‐donor kidneys and to have longer cold ischaemic times. Recipients with pre‐operative hypoalbuminaemia had longer hospital admissions post‐operatively but no difference in delayed graft function rates. There was no difference in 1 year creatinine but recipients with hypoalbuminaemia had reduced risk for cellular rejection. We observed significantly worse patient survival (83.2% vs 90.7%, P < 0.001) and overall graft survival (72.5% vs 82.0%, P < 0.001) for recipients with hypoalbuminaemia vs normal albumin levels, respectively, but no difference in death‐censored graft survival. In a Cox regression model, adjusted for baseline pre‐operative variables, hypoalbuminaemia was independently associated with an increased risk for overall graft loss after kidney transplantation (hazard ratio 1.468, 95% confidence interval 1.087–1.982, P = 0.012). Conclusion: Pre‐operative hypoalbuminaemia is an independent risk factor for overall graft loss after kidney transplantation. Further work is warranted to investigate the underlying pathophysiology to determine what supportive measures can be undertaken to attenuate adverse post‐transplant outcomes. SUMMARY AT A GLANCE: Low serum albumin is associated with adverse outcomes in many clinical settings. In this single‐centre retrospective cohort study of 1131 kidney transplant recipients, pre‐operative hypoalbuminaemia (<35 g/L) was an independent predictor of graft loss and patient death. Whether interventions to address the causes of hypoalbuminaemia might improve outcomes warrants further investigation.